صراع النفوذ الروسي- الأميركي على منطقة آسيا الوسطى – قزوين - العيسى, دريد (Latakia University Journal - Economic and Legal Sciences Series, 2018)
ركزت الدراسة على توضيح أبعاد الثقل الجيو-استراتيجي لمنطقة آسيا الوسطى – قزوين ، والذي جعلها في دائرة التنافس الإقليمية على وجه العموم ، والتنافس بين روسيا والولايات المتحدة الأميركية على وجه الخصوص. فآسيا الوسطى هي مكسر العصا بين قوتين، الأولى هي روسيا الطامحة لاستعادة نفوذها ومكانتها على الساحة العالمية والثانية أميركا الساعية لتطويق وتقييد نفوذ سابقتها والمحافظة على نفسها، القطب الوحيد المهيمن في العالم . ومنه فإنَّ الصراع في آسيا الوسطى ليس صراعاً فقط على الجغرافيا ومصادر الطاقة فحسب بل هو بالدرجة الأولى صراعاً على النفوذ و قواعد السيطرة . The study focused on clarifying the dimensions of gravity geo-strategic region of Central Asia - the Caspian, which make it in the regional competition on the circuit in general, and the rivalry between Russia and the United States in particular. Central Asia is Crushed stick between two, the first is Russia who aim to restore its influence on the world stage and the second America seeking to surround and restrict the influence of its predecessor and maintain itself only pole dominant position in the world so the conflict in Central Asia is not only a struggle only on geography and sources of energy, but is primarily a struggle for influence and control rules.